Pendampingan Masyarakat Lansia Desa Tanjung Melalui Edukasi Kegamaan Pada Kegiatan Sarwah - Muzakki, Ahmad; wahyudi, Fahris; Hidayatullah, Moh.; Ilman, Robith; Wahyudi , Wahyudi; Nujum, Mohammad; Faisal, Ahmad; kamarang, Apliandi; Bahri, , Moh Syaiful; Maulana Zidane, Yusuf; Shafi, Muhammad; Iskandar, Nur Moh; imron, Muhammad; Irsyam, Muhammad Haikal; Aliffullah, Muhammad; karim, M. Abdul; M. Arman, M. Arman; Rizal, Moh Nur; Yaqin, Ainul (Najah: Journal of Research and Community Service, 2024)
“Assisting the Elderly Community in Tanjung Village through Religious Education with the ABCD Method aims to improve the participation and spiritual quality of life of the elderly. The first stage, Discovery, identifies community potential through interviews and mapping. The Dream stage involves the community in envisioning the expected future, including increased religious activities at the Baitur Rohim Mosque. The Design stage involves designing strategies, processes and systems to activate spiritual and cultural assets, especially through religious activities. The Destiny stage evaluates and implements changes, ensuring sustainability through collaboration with students and lecturers. UNZAH students are important supporters with their religious understanding and religious experience. Challenges included limited access to information and social engagement of older adults. Reflection and continuous learning highlighted the importance of capacity building, resource optimization, external cooperation, technology integration and cultural approaches. Despite these obstacles, the mentoring has had a positive impact on the religious participation, spiritual quality of life, and social dynamics of the elderly community. Holistic and sustainable assistance is expected to be a positive legacy in the form of sarwah for future generations”.